Pengaruh Likuiditas dan Perputaran Modal Kerja terhadap Profitabilitas pada PT. Intan Komunikasi Indonesia di Tangerang - Widya Intan Sari; Noryani Noryani; Asep Muhammad Lutfi (Prodi Akuntansi STIE Hidayatullah Depok, 2021)
This study aims to determine the effect of liquidity and working capital turnover on profitability at PT. Indonesian Communication Diamond in Tangerang. The method used is explanatory research with analytical techniques using statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this study Current Ratio has a significant effect on Return on Assets of 32.6%, hypothesis testing is obtained t count > t table or ( 4.055 > 1.691). Net Working Capital has a significant effect on Return on Assets of 29.6%, hypothesis testing is obtained t count > t table or (3.780 > 1.691). Current Ratio and Net Working Capital simultaneously have a significant effect on Return on Assets with the regression equation Y = 9.045 + 0.740X1 + 0.446X2 and the contribution of the influence is 42.9%, hypothesis testing is obtained F count > F table or (15.958 > 2.890).